Dual gold catalysis - Hashmi, A. Stephen K. (Accounts of chemical research, 2014)
For more than a decade the innovative field of homogeneous catalysis by gold was dominated by the interaction of the substrate molecule with one gold center, in most cases in mononuclear gold complexes. The initial interaction was typically a π-coordination of a carbon-carbon double bond to the gold, an activation of the unsaturated substrate molecule by a π-acidic metal center. Only recently clear evidence for reactions that involve the activation of organic substrates by two gold centers was obtained...